Do Party Ties Increase Transfer Receipts in Cooperative Federalism? - Evidence from Germany - Yannick Bury; Lars P. Feld; Ekkehard A. Köhler (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Cooperative fiscal federalism needs a multi-level consent to decide on the allocation of intergovernmental transfers. We study how parliamentary representation of municipalities on the federal level influences the allocation of federal transfers to municipal governments under this type of federalism. Using a regression discontinuity design in close electoral races, we find that a directly elected member of the federal parliament, who belongs to the party that leads the federal government, induces higher infrastructure transfers from the federal government to a local jurisdiction. However, our results show that this effect only unfolds, if the parliamentarian's party is simultaneously leading the state government. Moreover, we identify party competition on the local level as motive behind the strategic use of federal funds. Thus, while supporting the swing voter hypothesis, our results suggest that federalism inherently entails restrictions for misusing intergovernmental transfers for political reasons.
Keywords: H71; H72; H77; E62; 330; fiscal federalism; partisan alignment; vertical transfers